2021- CSA Monitoring/Midline: Olopa Climate-Smart Village (Guatemala) - Bonilla-Findji, Osana; Eitzinger, Anton; Martínez Barón, Deissy; Martínez Salgado, Jesus David; López, Claudia; Guevara, Melvin (2022)
This dataset contains the files produced in the “adjusted” implementation (see Note below) of the standard “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Olopa Climate-Smart Village (Guatemala) in August-September 2021